2020
DOI: 10.1007/s12062-020-09278-3
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Home Mobility and Social Participation of Older People: a Photo-Based Ambulatory Assessment Study

Abstract: Research has shown that social participation contributes to older people's healthy ageing. Out-of-home mobility may promote higher levels of social participation among older people. However, mobility and social participation are sophisticated constructs. Social participation can be distinguished among different levels, such as being alone, being alone surrounded by others, interacting with others or engaging in activities together. Social participation and time spent in out-ofhome-mobility can be difficult to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 60 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…A photo-based ambulatory assessment study revealed that there are older people who spend most of their time engaged in activities without interaction, leading to feelings of loneliness. Additionally, there are older individuals who spend less time in social interaction and those who spend the most time outside of their homes helping others or participating in community activities [65].…”
Section: Exploring the Impact Of Social Factors On Longevity And The ...mentioning
confidence: 99%
“…A photo-based ambulatory assessment study revealed that there are older people who spend most of their time engaged in activities without interaction, leading to feelings of loneliness. Additionally, there are older individuals who spend less time in social interaction and those who spend the most time outside of their homes helping others or participating in community activities [65].…”
Section: Exploring the Impact Of Social Factors On Longevity And The ...mentioning
confidence: 99%